Range expansion and contraction of Tillandsia landbeckii lomas in the hyperarid Chilean Atacama Desert indicates ancient introgression and geneflow - Koch, Marcus; Kiefer, Christiane; Möbus, Johanna; Quandt, Dietmar; Merklinger, Felix Franz; Harpke, Dörte; Villasante Benavides, Francisco (Perspectives in plant ecology, evolution and systematics, 2022)
Among the fascinating and highly specialized vascular plants in the hyperarid core of the Chilean and Peruvian Atacama Desert there are few Tillandsia species from the bromeliad family (Bromeliaceae). These grow epiarenically on bare sand without a functional root system, and in some rare cases they build up a monospecific and often the only landscape characterizing vegetation type, which is called Tillandsiales or Tillandsia loma. Tillandsia landbeckii is the dominating epiarenic species in Chile totally dependent on fog serving as the only water resource. Herein we elaborate on the hypothesis that migration and multiple colonization in concert with putative introgression from other Tillandsia species build up the present day phylogeographic distribution pattern and may contribute to the evolutionary dynamics and long-term success in hyperarid desert systems. Genomic analyses using GBS (genotyping-by-sequencing) data from the nuclear and plastid genome were conducted at the population level. A genome skimming approach was used to generate reference plastome data. The results indicate that both, multiple colonization and secondary contact of old gene pools and interspecies geneflow, contribute to present-day population genetic structure. Local-scale analysis also indicates that these past footprints of evolutionary history do contribute to present-day local adaptive potential of the species.